Comparative functional characterization of novel non-syndromic GJB2 gene variant p.Gly45Arg and lethal syndromic variant p.Gly45Glu - Juan Rodriguez-Paris; Jörg Waldhaus; Jeenal A. Gordhandas; Lynn Pique; Iris Schrijver (PeerJ, 2016)
We characterized a novel GJB2 missense variant, c.133G>A, p.Gly45Arg, and compared it with the only other variant at the same amino acid position of the connexin 26 protein (Cx26) reported to date: c.134G>A, p.Gly45Glu. Whereas both variants are associated with hearing loss and are dominantly inherited, p.Gly45Glu has been implicated in the rare fatal keratitis-ichthyosis-deafness (KID) syndrome, which results in cutaneous infections and septicemia with premature demise in the first year of life. In contrast, p.Gly45Arg appears to be non-syndromic. Subcellular localization experiments in transiently co-transfected HeLa cells demonstrated that Cx26-WT (wild-type) and p.Gly45Arg form gap junctions, whereas Cx26-WT with p.Gly45Glu protein does not. The substitution of a nonpolar amino acid glycine in wildtype Cx26 at position 45 with a negatively charged glutamic acid (acidic) has previously been shown to interfere with Ca2+ regulation of hemichannel gating and to inhibit the formation of gap junctions, resulting in cell death. The novel variant p.Gly45Arg, however, changes this glycine to a positively charged arginine (basic), resulting in the formation of dysfunctional gap junctions that selectively affect the permeation of negatively charged inositol 1,4,5-trisphosphate (IP3) and contribute to hearing loss. Cx26 p.Gly45Arg transfected cells, unlike cells transfected with p.Gly45Glu, thrived at physiologic Ca2+ concentrations, suggesting that Ca2+ regulation of hemichannel gating is unaffected in Cx26 p.Gly45Arg transfected cells. Thus, the two oppositely charged amino acids that replace the highly conserved uncharged glycine in p.Gly45Glu and p.Gly45Arg, respectively, produce strikingly different effects on the structure and function of the Cx26 protein.